Modeling citizenship : Jewish and Asian American writing - Schlund-Vials, Cathy J., 1974- (Temple University Press, 2011)
Navigating deftly among historical and literary readings, Cathy Schlund-Vials examines the analogous yet divergent experiences of Asian Americans and Jewish Americans in Modeling Citizenship. She investigates how these model minority groups are shaped by the shifting terrain of naturalization law and immigration policy, using the lens of naturalization, not assimilation, to underscore questions of nation-state affiliation and sense of belonging. Modeling Citizenship examines fiction, memoir, and drama to reflect on how the logic of naturalization has operated at discrete moments in the twentiet.